IMPROVING STUDENTS™ READING COMPREHENSION ACHIEVEMENT IN NARRATIVE TEXT THROUGH PAIRED STORY TELLING TECHNIQUE - Siregar, Hafizah -; Gurning, Busmin - (Universitas Negeri Medan, 2014)
Abstract This study attempted to improve students™ reading comprehension achievement in narrative text through paired story telling technique. This study was conducted by using classroom action research. The subject of the research was class XI SMA PAB 1 Medan which consisted of 25 students. The research was conducted in two cycles and every cycle consisted of three meetings. The instruments for collecting the data were quantitative data (Reading test) and qualitative data (diary notes, observation sheet and questionnaire sheet). Based on reading scores, students™ score kept improving in every evaluation. In the test I the mean was 65.28 in the test II the mean was 71.16. Based on observation sheet it was found that teaching-learning process ran well. Students were active, enthusiastic, and interested in reading. The result of the research showed that applying paired story telling significantly improved students™ reading comprehension achievement. Keywords: Reading comprehension achievement, paired story telling technique, senior High School™s Students